Unwanted neighbours - Flores, Jorge Manuel, 1964- (New Delhi, India)
xxii, 301 sayfa
Keywords: “In December 1572 the Mughal emperor Akbar arrived in the port city of Khambayat. Having been raised in distant Kabul, Akbar, in his thirty years, had never been to the ocean. Presumably anxious with the news about the Mughal military campaign in Gujarat, several Portuguese merchants in Khambayat rushed to Akbar's presence. This encounter marked the beginning of a long, complex, and unequal relationship between a continental Muslim empire that was expanding into south India, often looking back to Central Asia, and a European Christian maritime empire whose rulers considered themselves 'kings of the sea'. By the middle of the seventeenth century, these two empires faced each other across thousands of kilometres from Sind to Bijapur, with a supplementary eastern arm in faraway Bengal. Focusing on borderland management, imperial projects, and cross-cultural circulation, this volume delves into the ways in which, between c. 1570 and c. 1640, the Portuguese understood and dealt with their undesirably close neighbours-the Mughals“ --